Pola Komunikasi Interpersonal Ustaz Eka Permana Habiillah di Masjid Ar-Risalah - Sunandar, Rizal; Wahyudin , Aep; Fatoni , Uwes (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to (1) the characteristics of interpersonal communication (2) the form of interpersonal communication and (3) the purpose of interpersonal communication. This research uses interpersonal communication theory. While the method used is descriptive method. The results that the authors get in this study is a match between the theory and the phenomena obtained after conducting observations and interviews. The characteristics, (1) starting from the personal self, (2) being transactional religious, (3) the content of the message of da'wah and interpersonal relationships, (4) physical closeness, (5) interdependent or interdependent. In the form of communication used in the form of small group communication. The goals are (1) enjoining good and bad deeds, (2) knowing yourself, (3) getting to know the field of da'wah, (4) spreading the message of peace, (5) seeking pleasure, (6) eliminating harm.